Disease Impact, Diagnostic Delay, and Unmet Medical Needs of Patients With Cholinergic Urticaria in German-Speaking Countries - Altrichter, Sabine; Mellerowicz, Emilia; Terhorst-Molawi, Dorothea; Grekowitz, Eva; Weller, Karsten; Maurer, Marcus (Frontiers in Allergy, 2022)
Abstract Background Cholinergic urticaria (CholU) is a common type of chronic inducible urticaria. Little is known about the burden of the disease and its unmet medical needs. Aim To characterize the unmet medical needs of CholU patients. Methods Patients with CholU (n = 111) took part in a German online-survey that assessed their symptoms, diagnostic delay, impact on daily-life,quality of life and their experience with physician care. Results Virtually all patients reported typical signs and symptoms of CholU, i.e. whealing, (93.7%) and itch (91.9%) in response to typical trigger situations such as physical activity, passive warming or stress. Despite this, patients reported a marked diagnostic delay of 30.2 months (range 0 to 279 months). Only 38% of the patients received a blood examination, and only 16% underwent provocation testing for diagnosing CholU, as recommended by the international guideline. Physician contacts were common, but patient satisfaction with their disease management was low. 90.1% of the patients stated to have an uncontrolled disease, resulting in a strong impact on their everyday activities, sleep, and quality of life. Conclusion Patients with CholU exhibit many important unmet needs, and improvement in the diagnostic work up and patient care is needed, as are better treatment options.